Recurrence of Asymptomatic COVID-19 after Recovery among Healthcare Workers - Cucunawangsih Cucunawangsih; Ratna Sari Wijaya; Nata Pratama Hardjo Lugito; Ivet Suriapranata (Case Reports in Infectious Diseases, 2022)
We describe five healthcare workers (HCWs) with a recurrence of asymptomatic SARS-CoV-2 infection at Siloam Teaching Hospital, Indonesia. All cases involved nurses, with an average age of 27 years. The RT-PCR assay confirmed the first and second infection episodes. All cases showed negative RT-PCR results in the period between two infection episodes. The median interval time between two infection episodes was 123 days, ranging from 92 to 158 days. The clinical outcomes for all cases were favourable, with no mortality observed among study cases. Further studies will be required to understand the true nature of this phenomenon.